Pola Asuh Anak, Kesegaran Jasmani Remaja, Dan Implikasinya Terhadap Pendidikan Agama Kristen - Freud Tumiur Panjaitan Freud Panjaitan (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
This study is about the parenting behaviour on improving the children’s physical fitness and its implication on Christian religion education and it was done at Universitas Kristen Indonesia. The purpose of doing this study is finding out the parenting behaviour on improving the children’s physical fitness and its implication on Christian religion education. The method of the study used was library research, where the researcher is the key instruments, in collecting the data of the research, books, journal, articles and other sources related to the topic of this study were read in order to answer the question of this study. These sources were taken ofline and online. The online sources were derived directly from google scholar web. The result of this study shows that the best parenting types of all is authoritative parenting, which is a combination of authoritarian parenting and permissive parenting. Then it is concluded that in order to improve the children’s physical fitness, parents should use authoritative parenting, and when the children’s physical fitness getting better, the implication on Christian religion education is getting better.